2002
DOI: 10.1381/096089202321019639
|View full text |Cite
|
Sign up to set email alerts
|

The Laparoscopic Adjustable Gastric Band (Lap-Band<SUP>®</SUP>): A Prospective Study of Medium-Term Effects on Weight, Health and Quality of Life

Abstract: Placement of the Lap-Band system provides safe and effective control of severe obesity. The effect on weight loss is durable and is associated with major improvement in health and quality of life. It has the potential to provide a broadly acceptable option for this common and serious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
175
1
15

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 341 publications
(204 citation statements)
references
References 24 publications
13
175
1
15
Order By: Relevance
“…22,23 It has a lower overall and major complication rate 24 than Roux-en-Y gastric bypass. Given the accessibility of LAGB in private clinics in and outside of Canada, it is important for general surgeons to be aware of the common presentations of LAGB complications.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 It has a lower overall and major complication rate 24 than Roux-en-Y gastric bypass. Given the accessibility of LAGB in private clinics in and outside of Canada, it is important for general surgeons to be aware of the common presentations of LAGB complications.…”
Section: Resultsmentioning
confidence: 99%
“…Bariatric surgery provides the most long-lasting results for those individuals in whom clinical strategies fail (9). Several parameters have been proposed to assess the outcomes of bariatric surgery (9,10). Surgeons have used the amount of weight loss as the main post-operative outcome, although the improvement of the multiple obesity-associated medical conditions should be considered, including physical and psychological parameters (11).…”
Section: Methodsmentioning
confidence: 99%
“…The Medical Outcome Study 36-Item Short-Form Health Survey (SF-36) was designed for clinical practice and research (14), and validated in several populations (15)(16)(17). In studies conducted in the US, the SF-36 was used as the gold standard for QoL assessment (10). The same instrument employed in studies of individuals undergoing bariatric surgery (18,19) was considered a useful tool for population-based surveys and for the evaluation of health policies.…”
Section: Methodsmentioning
confidence: 99%
“…Ren et al (49) reported weight loss comparable with gastric bypass and acceptably low complications. Data also show marked improvement in comorbidities (49,50) and quality-of-life measures (49,51). The most significant late complications (i.e., gastric pouch dilation and gastric prolapse) have been greatly reduced by use of the pars flaccida technique (52)(53)(54)(55)(56).…”
Section: Restrictive Proceduresmentioning
confidence: 97%